The Effect Of Various Sun Time Under Exposure To Ultraviolet Light Of The Sun On Interleukin 10 Cytokine - Rachmad Bayu Kuncara (Jurnal Biosains Pascasarjana, 2022)
Sunbathing activities are often found to occur during the severe acute respiratory syndrome coronavirus 2 (SARS CoV2) pandemic that causes Corona Virus Disease 2019 (COVID 19). IL-10 is an inhibitory cytokine for macrophages and dendritic cells that play a role in controlling non-specific and cellular immune reactions. The purpose of this study was to explain the immunosuppression by the cytokine interleukin 10 which is often found to occur due to sun exposure. This research method is an experimental study with a completely randomized design (CRD). The research design used was a randomized post test only control group design. Data were analyzed using the Kruskal Wallis test with statistical test results obtained p value 0.550 (> 0.05) meaning there was no difference in the levels of cytokine interleukin 10 in each treatment group.